Numerical Study of Slamming Loads on Bow Flare of FPSO Model by Irregular Waves - Young Jun Kim; Kyong-Hwan Kim; Bo Woo Nam; Sa Young Hong; Yoon-Jin Ha (Journal of Marine Science and Engineering)
Numerical studies were performed to investigate bow flare slamming loads under irregular waves. To estimate the slamming forces in the simulations, two time windows were selected based on existing experimental data. This study examined horizontal and vertical slamming phenomena by analyzing the relationship between the motions and the resulting slamming forces. The horizontal and vertical slamming forces from the simulations were directly compared with the experimental data. Furthermore, the experiment and simulation results were compared against a representative classification code for additional validation. The findings provide insights into the physical phenomena of horizontal and vertical slamming and confirm that the formulation suggested by classification societies provides a reasonable estimation of slamming loads. Finally, the results emphasize that both horizontal and vertical slamming forces are significant design parameters.